Literatur Review : Penerapan Sintaks Model Pembelajaran Problem Solving Pada Kurikulum 2013 - Erika Erika; Astalini Astalini; Dwi Agus Kurniawan (Edumaspul: Jurnal Pendidikan, 2021)
This research is a literature study with descriptive qualitative research type with library research which seeks to describe the application of the syntax of problem solving learning models in the 2013 curriculum. In this literature study research the authors use various written sources such as articles, journals and relevant documents with the studies in this study. This study focuses on the application of problem solving learning model syntax. The results of the study show that the syntax of the problem solving learning model is not in accordance with the demands of the 2013 curriculum, it can be seen from the syntax that has not been able to improve the social attitudes of students. The next interesting research to be developed as research is the development of a problem solving learning model syntax to improve the social attitudes of students.